Prenatal exposure to bisphenol A causes reproductive damage in F1 male rabbits due to inflammation and oxidative stress - Qianhui Zhao; Jialu Pan; Yongzhan Bao; Xiao Wang; Wanyu Shi (Ecotoxicology and Environmental Safety)
Bisphenol A (BPA) is used extensively in producing industrial chemicals such as plastic products, resin, and paper coatings. Concerns have been expressed regarding its possible detrimental consequences, especially on the reproductive system of mammals. Despite extensive study in this domain, there has been no targeted examination of the impact of BPA on F1 generation rabbits. BPA exposure model was developed in pregnant female rabbits to examine the effects of BPA on reproductive hormones, cellular apoptosis, oxidative stress, inflammatory response, and tissue integrity in weaning rabbits. The results indicated that BPA exposure triggered an inflammatory response and oxidative stress, consequently impacting the reproductive system of weaned rabbits and altering reproductive hormone levels. By modulation of the Nrf2 and NF-κB axes, BPA could influence the expression of antioxidant enzymes and inflammatory mediators in the rabbit reproductive system, leading to cell apoptosis and tissue damage. These results underscore the importance of monitoring BPA exposure during pregnancy and emphasize the necessity of implementing measures to mitigate its potential effects on the reproductive health of offspring.